Developing Religious School Culture: Strategies and Impacts on Islamic Religious Education Outcomes - Latifatul Azizah; Saiful Amien; Moh. Nurhakim (AL-ISHLAH: Jurnal Pendidikan, 2025)
Religious culture in schools plays a vital role in shaping students’ moral character and supporting Islamic Religious Education (PAI) outcomes. This study explores the strategies used to develop religious school culture and evaluates their impact on students’ character development and academic performance in PAI. A qualitative case study was conducted at SD Muhammadiyah 1 Ngimbang-Lamongan, involving 10 participants including the principal, PAI teachers, and parents. Data were collected through observations, in-depth interviews, document analysis, and Focus Group Discussions (FGDs), then validated using source, technique, and time triangulation. Thematic analysis was conducted using Miles and Huberman’s interactive model. The findings revealed four core strategies: (1) creating a religious atmosphere (e.g., playing Islamic songs and murottal), (2) modeling religious behavior by teachers, (3) habituating Islamic practices (e.g., congregational and Dhuha prayers, tahfidz, and the 5S culture), and (4) innovation in extracurricular programs (e.g., Muhadloroh, Hizbul Wathon). These strategies positively contributed to students' discipline, spiritual awareness, Qur’anic memorization, and mastery of PAI materials. Developing religious culture through structured and consistent strategies fosters both academic and character excellence. The findings confirm the importance of integrating Islamic values into daily school practices and highlight the role of teacher modeling and school-family collaboration in sustaining religious values.